1995
DOI: 10.17761/ijyt.6.1.b3587167251j5k14
|View full text |Cite
|
Sign up to set email alerts
|

Centralization Phenomenon: Its Usefulness in Evaluating and Treating Referred Pain

Abstract: In patients with low-back and radiating leg pain, a clinical phenomenon has been described known as "centralization," which occurs during a mechanical evaluation protocol described by McKenzie. Relocation of the most distal pain in a proximal or central direction characterizes the pain behavior when patients are assessed in this fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 2 publications
1
14
0
2
Order By: Relevance
“…The centralization phenomenon is a common clinical sign observed when patients with low back pain are examined using standardized test movements and sustained postures first described by McKenzie (278). This phenomenon has been evaluated for reliability and validity in multiple contexts (279)(280)(281)(282)(283)(284). Investigators have found that the centralization phenomenon is highly specific to discogenic pain, and is infrequently observed in patients with sacroiliac or facet joint pain.…”
Section: Discussionmentioning
confidence: 99%
“…The centralization phenomenon is a common clinical sign observed when patients with low back pain are examined using standardized test movements and sustained postures first described by McKenzie (278). This phenomenon has been evaluated for reliability and validity in multiple contexts (279)(280)(281)(282)(283)(284). Investigators have found that the centralization phenomenon is highly specific to discogenic pain, and is infrequently observed in patients with sacroiliac or facet joint pain.…”
Section: Discussionmentioning
confidence: 99%
“…None of these methods has proven superiority over another, and none provides significant neurogenic claudication improvement. 18,19 If there is a history of lower limb chronic pain, paresthesia, dysesthesia, or neuropathic pain, this treatment can be associated with tricyclic antidepressants and/or anticonvulsants such as gabapentin or pregabalin. Pregabalin is the drug of choice in neuropathic pain, with 40% of patients reporting relief.…”
Section: Lumbar Spinal Stenosis: Conservative Treatmentmentioning
confidence: 99%
“…None of these methods has proven superiority over another, and none provides significant neurogenic claudication improvement. 18 19 …”
Section: Lumbar Spinal Stenosis: Conservative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As per Werneke et al [11], the centralization of symptoms supports favorable outcomes in patients. Although centralization is considered a predictor of the treatment outcomes in low back pain [11][12][13][14][15][16], limited studies have been conducted on patients with CBPS. It is observed that C5-C6 is the most affected segment in the cervical spine.…”
Section: Introductionmentioning
confidence: 99%